2012
DOI: 10.3109/10428194.2011.647017
|View full text |Cite
|
Sign up to set email alerts
|

Different immunoprofiles in patients with chronic myeloid leukemia treated with imatinib, nilotinib or dasatinib

Abstract: Immunomodulation induced by dasatinib is reportedly related to better prognosis in chronic myeloid leukemia (CML). However, the underlying mechanism has not yet been fully elucidated. The immunoprofiles of 63 patients in the chronic phase of CML were evaluated during treatment with a tyrosine kinase inhibitor (imatinib, n = 36; nilotinib, n = 9; dasatinib, n = 18). The numbers of CD56 + CD57 + and CD3 + CD57 + cells increased significantly in the dasatinib group. The numbers of regulatory T-cells were comparab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 16 publications
2
49
0
Order By: Relevance
“…In addition, dasatinib reduces the adhesion of neutrophils to blood endothelium, perhaps contributing to the increased accumulation of these cells in blood over the course of the treatment and accounting for the observed increased granulocyte counts (29). The secretion of granulocyte-macrophage colony stimulating factor (GM-CSF) has also been shown to be increased by dasatinib treatment (30). Previously, Fraser and colleagues (31) reported that a higher dose of dasatinib (25 mg/kg/day) reduced the number of extrapulmonary B16.OVA metastases compared with a lower dose (5 mg/kg/day).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, dasatinib reduces the adhesion of neutrophils to blood endothelium, perhaps contributing to the increased accumulation of these cells in blood over the course of the treatment and accounting for the observed increased granulocyte counts (29). The secretion of granulocyte-macrophage colony stimulating factor (GM-CSF) has also been shown to be increased by dasatinib treatment (30). Previously, Fraser and colleagues (31) reported that a higher dose of dasatinib (25 mg/kg/day) reduced the number of extrapulmonary B16.OVA metastases compared with a lower dose (5 mg/kg/day).…”
Section: Discussionmentioning
confidence: 99%
“…1 of CML patients, collected at the time of diagnosis, were incubated for 4 hours with NK cells, isolated from the same patients after achieving complete cytogenetic response (see Table 1 Of note, dasatinib, in contrast to nilotinib, inhibited NK cell function in ADCC assays, most likely because of inhibition of Src family kinases as reported previously. 38,39 In vivo dasatinib treatment, in contrast, might cause positive immune-modulatory effects, such as enhanced NK cell activity 40 and clonal expansion of large granular lymphocytes. 41,42 Accordingly, NK cells isolated from 2 dasatinib-treated patients did not show any deficit in conferring CSL362-mediated ADCC.…”
Section: /Cd38mentioning
confidence: 99%
“…Local accumulation of Tregs in malignant tissue or a higher proportion of Tregs in peripheral blood has been reported in a variety of tumors from different tissues and organs, and these higher Treg activities have been associated with poor clinical outcomes [24][25][26]. Mustjoki et al [10] revealed that dasatinib-treated patients with LGL lymphocytosis exhibited a lower proportion of Tregs in peripheral blood, and others examined the differences of Treg ratios among TKIs, with conflicting results [18,20]. In our study, there were no differences in the proportion of Treg cells between dasatinib-treated patients and patients treated with other TKIs.…”
Section: Discussionmentioning
confidence: 98%
“…Second-generation TKIs, especially dasatinib, not only show potent inhibitory effects for the target kinase (ABL), but also possess many off-target effects, which could be responsible for the different properties and adverse event profiles of each TKI [3,4]. Among these, the immunomodulatory effects of dasatinib have been of principal interest and the subject of vigorous investigation as the effects might directly influence the clinical outcome [13,[18][19][20].…”
Section: Discussionmentioning
confidence: 99%